The Application of Global Method with Picture Word Board Media to Improve The Beginning Reading Skills of Grade I Elementary School Students - Paryati; Wachid Bambang Suharto, Abdul (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Reading skills are basic skills for students that they must master in order to follow all activities in the education and learning process. Beginning reading is the initial reading given to children in grade I (one). The purpose of this study is to improve the beginning reading skills of grade 1 students as a basis for understanding further lessons. The method used is the PTK model developed by Kurt Lewin. Data analysis techniques are quantitative and qualitative. The obstacles faced include the fact that students' reading skills at the elementary school level tend to be low. This can be seen from the data on student learning outcomes in Indonesian language content in grade 1 SDN 2 Samudra Kulon. It is expected that